2021
DOI: 10.7554/elife.64179
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of retrovirus infection reveals a role for Siglec-1/CD169 in multiple routes of transmission

Abstract: Early events in retrovirus transmission are determined by interactions between incoming viruses and frontline cells near entry sites. Despite their importance for retroviral pathogenesis, very little is known about these events. We developed a bioluminescence imaging (BLI)-guided multiscale imaging approach to study these events in vivo. Engineered murine leukemia reporter viruses allowed us to monitor individual stages of retrovirus life cycle including virus particle flow, virus entry into cells, infection a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Thus, our work shows that the gammaretrovirus MLV can infect non-dividing cells like DCs, thought to be the initial in vivo targets of MLV [12, 13, 43]. Interestingly, previous studies have suggested that gammaretroviruses can infect other quiescent cell types, such as neurons [44].…”
Section: Discussionmentioning
confidence: 79%
“…Thus, our work shows that the gammaretrovirus MLV can infect non-dividing cells like DCs, thought to be the initial in vivo targets of MLV [12, 13, 43]. Interestingly, previous studies have suggested that gammaretroviruses can infect other quiescent cell types, such as neurons [44].…”
Section: Discussionmentioning
confidence: 79%
“…Thus, our work shows that the gammaretrovirus MLV can infect non-dividing cells like DCs, thought to be the initial in vivo targets of MLV [ 12 , 13 , 44 ]. Interestingly, previous studies have suggested that gammaretroviruses can infect other quiescent cell types, such as neurons [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we adoptively transfected DiR-labeled spleen-derived iNKT cells with specific phenotypes and functions into normal DBA/1 mice and tracked the migration, distribution, and metabolism of iNKT cells in mice using a small animal imaging technique. Previous studies have reported that tail vein injection results in fluorescence in organs such as the liver and spleen within 30 seconds [ 26 ]. We observed that strong fluorescence can be detected in the lungs immediately after cell infusion, and the fluorescence intensity was the strongest at 10 min and then gradually weakened.…”
Section: Discussionmentioning
confidence: 99%